Synthesis, Binding and Fluorescence Studies of Bis-2-amidopyrrole Receptors for Bis-carboxylate Anions - Emilio Calle; Belén Jiménez; Cruz Caballero (Sensors, 2009)
The ditopic neutral receptors 1 and 2 were synthesized for the recognition and sensing of bis-carboxylates. They are based on pyrrole and amide groups as hydrogen-bond donors to bind the oxoanions of the guests. Among the obtained results, the selectivity for glutarate over succinate is particularly interesting.Compound 1 behaves as a PET fluorescence sensor for glutarate.